If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7y = mx + yb Reorder the terms: 2x + 7y = by + mx Solving 2x + 7y = by + mx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1mx' to each side of the equation. 2x + -1mx + 7y = by + mx + -1mx Reorder the terms: -1mx + 2x + 7y = by + mx + -1mx Combine like terms: mx + -1mx = 0 -1mx + 2x + 7y = by + 0 -1mx + 2x + 7y = by Add '-7y' to each side of the equation. -1mx + 2x + 7y + -7y = by + -7y Combine like terms: 7y + -7y = 0 -1mx + 2x + 0 = by + -7y -1mx + 2x = by + -7y Reorder the terms: -1by + -1mx + 2x + 7y = by + -7y + -1by + 7y Reorder the terms: -1by + -1mx + 2x + 7y = by + -1by + -7y + 7y Combine like terms: by + -1by = 0 -1by + -1mx + 2x + 7y = 0 + -7y + 7y -1by + -1mx + 2x + 7y = -7y + 7y Combine like terms: -7y + 7y = 0 -1by + -1mx + 2x + 7y = 0 The solution to this equation could not be determined.
| 4a-a+3= | | -4-4y=3x | | 8y-5y=9 | | 3x+196=11x-12 | | -2x+16y=-34 | | -7(1-8k)=-231 | | 63x^2-45x=0 | | U+(-14u)-(-16u)=-18 | | 7b-5b=20 | | 20q+12q+(-18q)-6q=-16 | | 20-5y=-4x | | (5x+7)(5x+3)=0 | | 2h^2+28h-98=0 | | 5d-3.3=7.3 | | 3l+6=55 | | x^4-4x^3-x^2-16x-20=0 | | 49v^2-100=0 | | -3(6p+2)-3=-117 | | 20q+12q+(-18)-6q=-16 | | 0=560t-16t^2 | | (3*2)3-7*3= | | 7v-(-v)-13v-4v+5v=16 | | 18m^2-32=0 | | 1-0.4r=0.3-0.3r | | -3-27a=-3(2a-3) | | 12+4(z-3)=4z+5 | | -7(n+4)+30=-3n-18 | | 6a+5(14)=94 | | 6x-13+2x+1=90 | | x^4-4x-12=0 | | 48-16=4(x-6) | | 3x-6+130+8x+4=180 |